The impact of organizational sustainability on organizational reputation An applied study in the General Company for Iraqi Cement - Southern Cement Associate - Al-Sharifi, Zainab Hadi Maaouf; Al-Enzi, Ameera Khudair Kadhim (Al-Ghary Journal of Economic and Administrative Sciences, 2022)
The study aimed to explore the relationship between organizational sustainability through its dimensions [economic sustainability, social sustainability and environmental sustainability], and organizational reputation with its dimensions [Emotional Appeal, Products and Services, vision and leadership, Workplace Environment, and Financial Performance]. The General Company for Iraqi Cement in the city of Kufa was chosen as a community to conduct the study, and the sample size was (127), one of the employees of the mentioned company. For the purpose of analyzing the data and testing the hypotheses of the study, the statistical program (SmartPls) was relied on.The study concluded that there is an impact relationship of organizational sustainability on organizational reputation, meaning whenever a company adopts high levels of sustainability, this improves its reputation in the community